Chemical analysis and chemical imaging of fragrances and volatile compounds by low‐temperature plasma ionization mass spectrometry. (9th July 2013) - Campbell, Dahlia I.; Dalgleish, Jon K.; Cotte‐Rodriguez, Ismael; Maeno, Shuji; Graham Cooks, R.
Abstract : RATIONALE: The rapid analysis of volatile compounds, such as fragrances, is important in many commercial industries. The various ambient ionization methods have until now been largely applied to non‐volatile or low‐volatile compounds with success, and this study develops a semi‐quantitative method for volatile compounds in commercial cleaning products. METHODS: Low‐temperature plasma (LTP) ionization was used to perform rapid analysis, determine limits of detection (LODs) and perform chemical imaging on eight fragrances. Several mass analyzers including an ion trap, a quadrupole and an orbitrap were used to rapidly screen volatile compounds from cloth, paper, and glass and determine compositions present in a commercial cleaning product. Peltier cooling was used in some cases to enhance the retention time of compounds on a surface. RESULTS: This LTP method allowed the detection of fragrances in low picogram absolute amounts from glass, paper and cloth. Quantitation was demonstrated for compounds in a commercial cleaning product 1 min after the product was applied to a vinyl tile surface. High‐throughput analysis and simultaneous detection of multiple compounds in a mixture were demonstrated with analysis times of less than 1 min. Modest spatial resolution (better than 1 cm) was achieved with LTP ionization. CONCLUSIONS: A semi‐quantitative method has been demonstrated for the routine analysis of volatile and semi‐volatile compounds. This method would be useful in quality control and production environments to determine product persistence, location of analytes and to complement olfactory studies for determining concentrations in the ambient environment. Copyright © 2013 John Wiley & Sons, Ltd.